Scholastic Children Thesaurus - Bollard, John. K.; Nang Chan Yeema (New York, USA Scholastic Inc., 1998)
Presents a list of alphabetically arranged words with several synonyms and an illustrative sentence for each.
Keywords: Juvenile Nonfiction